Silica-supported ionic liquid-based dispersive microextraction of grapefruit peel flavonoid (hesperidin) and assessment of its antioxidant activities - Waheed, Ammara; Akram, Sumia; Waseem, Faizan; Iqbal, Asif; Ashraf, Rizwan; Anwar, Farooq; Ismail, Sarang; Mushtaq, Muhammad; Mubarak, Nabisab Mujawar; Hosseini-Bandegharaei, Ahmad (Oxford University Press, 2025)
The present research explores the application of dispersive liquid–liquid microextraction (DLLME) of hesperidin (HSP) from grapefruit peel (GFP) while using silica-supported ionic liquids (ILs) as a stationary phase. The ILs [Et3NH][HSO4], Benzalkonium chloride, and didecyldimethyl ammonium chloride were immobilised on mesoporous silica support of particle size 150 micron. The parameters were optimised for the preparation of crude extracts. The extraction of GFP with a 50-mesh particle size using 1:1 (v/v) of 1% (v/v) acidified methanol (glacial acetic acid) and DMSO for 80 min at a liquid to solid ratio of 20 and 350 rpm shaking speed produced 18 g of crude extract/100 g of GFP. After using silica-supported IL as the stationary phase in a DLLME-based clean-up, an extract with 0.54 mg of HSP/g of crude extract was obtained upon elution with DMSO. Remarkably, 0.80 μg of HSP/g of crude extract was similarly recovered when IL was used as an eluent against a non-polar stationary phase. An enrichment factor for HSP equivalent to 2.1–3.4 was obtained by employing [Et3NH][HSO4] as a mobile phase against mesoporous silica or as a stationary phase supported on mesoporous silica. The findings support the great potential of silica-supported ILs as the stationary phase for DLLME.